The Intellectual Relations of Two Shiite Seminary in Qom and Ahwaz in the Second and Third Centuries - Mohammadreza Hedayatpanah; Qasem Khanjani (تاریخ اسلام)
Qom, Kufah and Bagdad being considered as the main centers of scientific activities of Shiites since the second until the forth century After Hijrah are of significant position in regard with the Shiism studies. Nevertheless, the Seminary of Ahwaz as one the ancient and significant Shiite schools in Iran is deserved to be mentioned here, since it has been of authorized and well-known representatives in the history of jurisprudence and tradition of Shi’ah in accordance with the historical, tradition and translation sources. Following a review on the origins of Shiism in Ahwaz, this article is to represent the scientific position of Ahwaz towards preserving and developing the school of Prophet’s family through the investigation of scientific relationship between Qom and Ahwaz. This relationship has been developed via the movement of some scholars from Ahwaz towards Qom and vice versa, the scientific discussions between the two great households of “Al e- Mahziyar e- Ahwazi” and Qom’s Ash’arites of” as well as the presence of some specific followers of Imams in these two centers.